Effects of Phytase Super Dosing on Performance, Plasma Mineral Contents and Bone Mineralization in Broiler Chicken - Hossain, S.; Hossain, M.A.; Akter, N.; Akter , M. (International Journal of Poultry Science, 2022)
Objectives: This experiment evaluated the effect of phytase super dosing on performance, tibia bone quality and serum biochemistry of broiler chicken. Materials and Methods: A total of 96 day-old chicks were distributed randomly into four treatment groups: D0, D1, D2, D3 with four replicates per treatment (6 chicks per replicate). The treatments were control diet (D0), control diet +500 FTU phytase kg–1 (D1), control diet +1500 FTU phytase kg–1 (D2) and control diet +2500 FTU phytase kg–1 (D3), that were fed to the birds from day 13-28. Birds were offered a commercial starter diet from day 0-12. Results: The different levels of phytase had no significant effect on body weight gain (BWG) and feed intake (FI). Supplementation of 1500 FTU phytase kg–1 of diet showed better (p